2022
DOI: 10.1186/s12967-022-03566-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of pyroptosis and ferroptosis extensively involved in autoimmune diseases at the single-cell transcriptome level

Abstract: Background Approximately 8–9% of the world’s population is affected by autoimmune diseases, and yet the mechanism of autoimmunity trigger is largely understudied. Two unique cell death modalities, ferroptosis and pyroptosis, provide a new perspective on the mechanisms leading to autoimmune diseases, and development of new treatment strategies. Methods Using scRNA-seq datasets, the aberrant trend of ferroptosis and pyroptosis-related genes were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 104 publications
0
63
1
Order By: Relevance
“…The understanding of the molecular effects of Se deficiency and supplemental Se intake on the immune system is more solid, as the Se status directly affects the expression of selenoproteins relevant to the immune system ( 62 64 ). The link extents to multiple levels, including quality control of newly synthesized proteins in the ER to prevent secretion of immunogenic misfolded proteins ( 65 , 66 ), a direct involvement of selenoproteins in intracellular lymphocyte signaling ( 67 69 ), and an effect of selenoproteins, particularly GPX4, on immune cell survival and protection against hyperactivation–induced ferroptosis ( 70 , 71 ). Given that severe Se deficiency is an established risk factor for autoimmune disease ( 72 74 ) and appears to influence mortality risk in critical illness ( 20 , 75 , 76 ), the consistent associations observed in this study support discussion of active supplementation of COVID-19 patients with severe deficiency to achieve reference concentrations ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the molecular effects of Se deficiency and supplemental Se intake on the immune system is more solid, as the Se status directly affects the expression of selenoproteins relevant to the immune system ( 62 64 ). The link extents to multiple levels, including quality control of newly synthesized proteins in the ER to prevent secretion of immunogenic misfolded proteins ( 65 , 66 ), a direct involvement of selenoproteins in intracellular lymphocyte signaling ( 67 69 ), and an effect of selenoproteins, particularly GPX4, on immune cell survival and protection against hyperactivation–induced ferroptosis ( 70 , 71 ). Given that severe Se deficiency is an established risk factor for autoimmune disease ( 72 74 ) and appears to influence mortality risk in critical illness ( 20 , 75 , 76 ), the consistent associations observed in this study support discussion of active supplementation of COVID-19 patients with severe deficiency to achieve reference concentrations ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, non-canonical (involving caspase 4/5) NLRP3 inflammasome activation, also leading to canonical NLRP3 inflammasome activation, appears unique for MIS-C [ 8 ]. If uninhibited, aberrant activation of pyroptosis leads to massive DAMPs release, able to amplify and perpetuate uncontrolled inflammatory immune responses, potentially leading to autoantibody formation and autoimmunity [ 24 ]. Stringent host regulation of NLRP3 inflammasome activation is necessary, to avoid detrimental inflammatory reactions, as seen in numerous autoinflammatory and autoimmune diseases [ 18 , 19 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…If uninhibited, aberrant activation of pyroptosis leads to massive DAMPs release, able to amplify and perpetuate uncontrolled inflammatory immune responses, potentially leading to autoantibody formation and autoimmunity [ 24 ]. Stringent host regulation of NLRP3 inflammasome activation is necessary, to avoid detrimental inflammatory reactions, as seen in numerous autoinflammatory and autoimmune diseases [ 18 , 19 , 24 ]. Thus, loss of control of inflammasome regulation in genetically predisposed children, could potentially pave the way towards MIS-C [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The iron homeostasis in the brain of MS patients is severely disrupted, resulting from iron overload in lesional myeloid cells and deep nuclei, as well as decreased iron concentration in normal white matter and chronic cortical lesions [ 10 ]. A recent single-cell sequencing analysis of brain cells isolated from MS patients showed that the expression levels of some important anti-ferroptosis genes in neurons and oligodendrocytes were lower than those in normal individuals [ 11 ]. GPX4 , a gene that plays a significant role in anti-ferroptosis, was found to be down-regulated in some cell types of MS patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent single-cell sequencing analysis of brain cells isolated from MS patients showed that the expression levels of some important anti-ferroptosis genes in neurons and oligodendrocytes were lower than those in normal individuals [ 11 ]. GPX4 , a gene that plays a significant role in anti-ferroptosis, was found to be down-regulated in some cell types of MS patients [ 11 ]. This was also confirmed in a previous study by Hu et al, which showed that GPX4 expression was generally reduced in the gray matter of MS and the spinal cord of experimental autoimmune encephalomyelitis (EAE) [ 12 ], the most commonly used experimental model for MS [ 13 ].…”
Section: Introductionmentioning
confidence: 99%